The voice of Luke : not even sandals : with devotional notes throughout - McLaren, Brian D., 1956-; Seay, Chris (Nashville, Tenn. : Thomas Nelson, 2007)
A retelling of the Gospel of Luke. "Not even sandals" recovers the passion, grit, humor, and beauty have been lost in our translations of Luke. Brian McLaren recaptures what was lost as he retells this spiritual adventure with power and grace to read like a screenplay. McLaren provides an overlay of historical and theological observations to enrich the story.
The Voice : a scripture project to rediscover the story of the Bible -- from title page.
Keywords: Luke, -- Saint; Bible -- Selections; Bible. -- Commentaries